DIVINITY CONCEPT IN THE TEACHING OF INAYAT KHAN: AN ANALYSIS BASED ON ISLAMIC BELIEF - Nozira binti Salleh; Prof. Madya Dr. Faudzinaim bin HJ. Badaruddin (Journal of Islamic, Social, Economics and Development, 2017)
The teachings of Inayat Khan or known as Universal Sufism are increasingly gaining the attention to the world community as it is believed to be a good alternative spiritual teaching for those who are seeking for peace and tranquility. His teachings apply the term of Sufism but its goal is universal in the beliefs, the practice of certain practices and the acceptance of followers regardless of race, religion, ancestry and nation. Therefore, his teachings are increasingly attentive and welcome to the world community in general and Muslims in particular in many countries such as Turkey, Pakistan, India, Indonesia and others. Hence, this study aims to identify and evaluate the concept of divinity in this teaching which is seen as the primary basis for it and at the same time, knowing its true teaching position in Islam. This study applies literature study only with reference to the Inayat Khan's books. The findings show that research on the divine concept in the teachings of Inayat Khan is very contrary to belief of Islam that holds the concept of tauhid as contained in the Quran and Sunnah.